Analisis Kepatuhan Pengambilan Ulang Obat Antihipertensi pada Pasien Program Rujuk Balik di Puskesmas X Kota Jambi - Dewi, Rasmala; Yulianis, Yulianis; Isman, Sindi Nurisa (Universitas Baiturrahim, 2024)
Hypertension is also called the silent killer characterized by continuously high blood pressure in the ratio of systolic blood pressure (TDS) ≥ 140 mmHg and diastolic blood pressure (TDD) ≥ 90 mmHg. This hypertension requires long-term treatment, therefore patient non-compliance in therapy can cause failure of hypertension treatment. To determine the level of patient compliance in hypertension treatment, it can be seen from the compliance of drug retrieval by analyzing the relationship to gender, age, and comorbidities. This research method is carried out non-experimentally and uses analytical descriptive methods. Data collection from the poly registration book for patients with the July 2023 reverse referral program which will be measured 6 times from July - December 2023 obtaining patients with a population of 411 patients and a sample of 218 patients. The results showed that women suffered more from hypertension (62.8%), the most age of hypertension ≥60 years (78.4%), and patients suffered from hypertension without comorbidities (60.6%). The most commonly used hypertension treatment was monotherapy (56.9%). The level of compliance of hypertensive patients in the referral program was high in the category of re-taking antihypertensive drugs (67.4%). The results of the analysis stated that there was a relationship between gender and age on compliance with taking antihypertensive medication. The conclusion of this study is that the level of compliance is included in the high category, and there is a relationship between gender and age on compliance with re-taking antihypertensive drugs.